Analytical Model for Light Modulating Impedance Spectroscopy (LIMIS) in All-Solid-State p-n Junction Solar Cells at Open-Circuit - Almora Rodriguez, Osbel; Miravet, Daniel; Matt, Gebhard; Garcia-Belmonte, Germà; Brabec, Christoph (Applied Physics Letters, 2020)
Potentiostatic impedance spectroscopy (IS) is a well-known tool for characterization of materials and electronic devices. It can be complemented by numerical simulation strategies relying on drift-diffusion equations without any equivalent circuit-based assumptions. This implies the time-dependent solutions of the transport equations under small perturbation of the external bias applied as a boundary condition at the electrodes. However, in the case of photosensitive devices, a small light perturbation modulates the generation rate along the absorber bulk. This work then approaches a set of analytical solutions for the signals of IS and intensity modulated photocurrent and photovoltage spectroscopies, intensity modulated photocurrent spectroscopy (IMPS) and intensity modulated photovoltage spectroscopy (IMVS), respectively, from one-sided p-n junction solar cells at the open-circuit. Subsequently, a photoimpedance signal named “light intensity modulated impedance spectroscopy” (LIMIS = IMVS/IMPS) is analytically simulated, and its difference with respect to IS suggests a correlation with the surface charge carrier recombination velocity. This is an illustrative result and the starting point for future more realistic numerical simulations.<br